1970
DOI: 10.3126/kumj.v6i4.1744
|View full text |Cite
|
Sign up to set email alerts
|

Chondrolipoma of tongue

Abstract: Although lipomas can occur in any part of the body, they are found infrequently in the oral cavity. Variants of lipoma have been described according to the type of tissue present; a lipoma with cartilaginous metaplasia is a chondrolipoma which is a rare variant. We describe a chondrolipoma of tongue in a 36 year old lady. Key words: Tongue, Chondrolipoma doi: 10.3126/kumj.v6i4.1745     Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 505-507

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…[ 15 19 ] While these lesions are usually diagnosed in older adults, they may originate at a younger age as some of these tumors including the present case have shown long duration of presentation. [ 14 15 17 ] There may be an actual bimodal age predilection as substantial number of cases (almost one-third including the present case) seem to originate in the first two decades of life[ 13 14 15 19 ] but a larger number of cases will be required to accept or refute this observation. This feature of chondrolipoma slightly differs from a conventional lipoma, which are rarely seen in the first two decades of life and are thought to make their appearance at the age when fat starts accumulating in inactive individuals.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…[ 15 19 ] While these lesions are usually diagnosed in older adults, they may originate at a younger age as some of these tumors including the present case have shown long duration of presentation. [ 14 15 17 ] There may be an actual bimodal age predilection as substantial number of cases (almost one-third including the present case) seem to originate in the first two decades of life[ 13 14 15 19 ] but a larger number of cases will be required to accept or refute this observation. This feature of chondrolipoma slightly differs from a conventional lipoma, which are rarely seen in the first two decades of life and are thought to make their appearance at the age when fat starts accumulating in inactive individuals.…”
Section: Discussionmentioning
confidence: 91%
“…A review of the PUBMED database revealed 14 such cases in English literature. [ 7 8 9 10 11 12 13 14 15 16 17 18 19 ] We have included only those cases which presented strictly within the oral cavity and histologically showed presence of only cartilaginous tissue in a predominantly mature adipocyte proliferation. The clinicopathological features of these cases including the present case have been summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chondrolipoma is a benign mesenchymal tumor where mature chondroid areas are observed as a result of cartilaginous metaplasia in lipoma (1). Chondrolipomas are most frequently seen in the breast and rarely in the head and neck region and are most commonly found in adults in the fifth and sixth decade (2,3).…”
Section: Introductionmentioning
confidence: 99%